PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TWO STAY TWO STRAY (TSTS) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SDN 033 SINTONG KECAMATAN TANAH PUTIH KABUPATEN ROKAN HILIR - Liliana, Liliana; Alpusari, Mahmud; Marhadi, Hendri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: this Research is done because its low of result study class Student IPA IV SDN 033 Sintong Kec. Tanah Putih value average 59,64 from 20 student, that yet to reach KKM many 12 people (60,0%) whereas who reach KKM only 8 people (40,0%). Formula of problem in research what is this the Cooperative Studying model-implement Two Stay type Two Stray (TSTS) can to level it result study class Student IPA IV SDN 033 Sintong Kec. Tanah Putih?. The Research is executed to semester even Year Lesson 2015/2016 to month March until April 2016. Subjek this penelitan is student IV SDN 033 Sintong Kec. Tanah Putih, with student's number 20 people, that consist from 10 man–man and 10 women heterogen's have ability. Design this research is Class Action Research (PTK). the Research is done in two cycles. data collection Instrument to research this is teacher's observation sheet and student also result test study. After to be applied the Cooperative Studying model Two Stay Type Two Stray (TSTS) so research result show that teacher's activity to undergo leveling from 66,67% I's cycle become 91,67% II's cycle. student's Activity also to undergo leveling from 62,5% I's cycle become 87,5% II's cycle. Result study student to undergo leveling from base skor with average 59,64 to level become 74,75 to UH 1 I's cycle, next to UH 2 II's cycle to level again become 82,75. Leveling Persentase average result study from base skor to UH II is 38,73%. Completing classicaly to undergo leveling from data the early who finish only 8 people (40%) to level the become who finish 14 people (70%) I's cycle. Next to level again become 18 people (90%) II's cycle. this research result To be based can to be concluded that the Cooperative Studying model-implement Two Stay Type Two Stray (TSTS) to to level it result study class student IPA IV Country SD 033 Sintong Kec. Tanah Putih, succeed be done examiner.Key Word : Two Stay Two Stray (TSTS), Result study IPA